Ca-Al-rich inclusions in three Antarctic CO3 chondrites, Yamato-81020, Yamato-82050 and Yamato-790992: Record of lowtemperature alteration - Kojima,Tomoko; Yada,Satomi; Tomeoka,Kazushige (National Institute of Polar Research, 1995)
P(論文) Ca-Al-rich inclusions (CAIs) in three Antarctic CO chondrites, Yamato (Y)-81020,Y-82050 and Y-790992 have similar overall textures; most CAIs are rimmed or concentric objects. However, there are considerable differences in mineralogy; almost all of the CAIs in Y-81020 consist of primary high-temperature phases such as melilite, anorthite, fassaite and spinel, while most of the CAIs in Y-82050 and Y-790992 contain major amounts of nepheline and lesser amounts of melilite and anorthite. CAIs in Y-790992 contain more nepheline than those in Y-82050. Small grains (<1μm in diameter) of troilite commonly coexist with nepheline. Spinel in Y-81020 is almost free of Fe, while those in Y-82050 and Y-790992 contain variable amounts of Fe (6 to 60 and 42 to 65 FeAl_2O_4 mol%, respectively). The texture of CAIs suggests that nepheline and troilite are secondary alteration products formed by replacing mainly melilite and anorthite. Spinel in CAIs and olivine in amoeboid olivine aggregates probably became enriched in Fe along with the alteration. As the alteration proceeded, fassaite and spinel were also replaced by nepheline, and perovskite was replaced by ilmenite and ulvospinel. Diopside remained unaltered even in the most heavily altered inclusions. Comparison of mineralogy before and after the alteration suggests that considerable amounts of Na, Fe, S and Cl were introduced into CAIs and some amounts of Ca and Mg were lost. Based on the amounts of nepheline, the relative degrees of alteration of CAIs are as follows : Y-81020<Y-82050<Y-790992. In order to compare the relationship between alteration of CAIs and thermal metamorphism on the parent body, metamorphic grades of the three CO chondrites were petrographically determined. The results indicate that the metamorphic grade increases in the same order as that of the degree of alteration of CAIs, i. e. Y-81020<Y-82050<Y-790992. Therefore, the results raise the possibility that alteration of CAIs may be related to thermal metamorphism which occurred ...